Developing a definition for islamic built environment in Malaysia by sieving through the interpretation of public opinion shapers - Norliza binti Mohd Isa (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2015)
As Islam is the nation's official religion, the government of Malaysia strives to adopt Islamic image in Malaysia's built environment. Yet, given Malaysia's heterogeneous society, are Islamic concepts been implemented correctly and appropriately in the construction of Malaysia's built environment? Therefore, the aim of this study is to develop the definition of Islamic built environment in Malaysia by sieving through the interpretation of Malaysian public opinion shapers referred as 'experts' in this study. The 'experts' are defined as those who are relevant as a Malaysian opinion shapers or related in the design process including (1) public and political figures or administrators, (2) professionals, (3) academicians and (4) Islamic scholars, from the variety of races and religion in Malaysian heterogeneous society. This study has employed descriptive and survey-based research designs rooted in qualitative research paradigms with two research techniques (1) Delphi Method and (2) Media Content analysis. The first research method used structured and semi-structured interviews for primary data collection. The second method used the Media Content analysis as supporting data collection. This study fulfilled the aims and objectives of the research by obtain firstly, a definition of 'Islamic built environment' that is in accords to the situation in Malaysia. The study has defined an appropriated 'Islamic built environment' in Malaysia is a correlation between the (3) three elements with the six (6) main themes and ten (10) indicators. The first elements are; a situation or setting that encompasses the combination of created elements (spaces, places and structures), secondly, the implementation of Islamic ideology to serve human needs and values and third, the concept considers the suitability of people's lifestyle (both Muslim and non-Muslim) by symbolizing spiritually and physically the essence of Islam. The six main theme are; T1- Associated with Local context, T2- Avoid Political Agenda, T3- Created by Spiritual and Values of Islam, T4- Translation of 'Tauhid, Jannah and Jamaah', T5- Not for Branding and T6- Escape from Identity Conflict. The second finding is a framework of indicator of factors that make an environment truly Islamic. The ten indicators are; Tolerance, Natural Environment, Social Need and Human Comfort, Religious Identity, Order, Economic, Hygiene, Jannah, and Safety. The third finding is the level of satisfaction with comment on problems and shortcomings of the implementation of the existing 'Islamic built environment' happening in Malaysia. Fourth, recommendations for improving efforts towards implementation of existing 'Islamic built environment' and finally the fifth a comparative study between the opinion of the 'experts'. The findings of this study hopefully will be beneficial to Malaysian administrators, developers and designers because it's provided a fair and representative definition of Islamic Built Environment in Malaysia as derived from selected Malaysian opinion shapers. It is congruent with the nature of Malaysian heterogeneous society and with Malaysian current agenda of 1 Malaysia and the concept of Islamic moderation.